Genomic integration of HHV-6 mimicking viral reactivation after autologous stem cell transplantation - rossana mineri; Jacopo Mariotti; Barbara Sarina; Lucio Morabito; roberto crocchiolo; stefania bramanti; tiziana sarno; federica tordato; carmelo carlo-stella; armando santoro; Luca Castagna (Mediterranean Journal of Hematology and Infectious Diseases)
The monitoring of HHV-6 after allogeneic hematopoietic stem cell transplantation (HSTC) has proven to be useful in preventing life-threatening complications; however, the pathogenic role of HHV-6 after autologous HSCT is not well-characterized, although viral reactivation might be responsible for significant complications even after autologous HSCT. Here we report for the first time to our knowledge the case of a patient with genomic integration of HHV-6, presenting with high titers of HHV-6 after autologous HSCT, mimicking HHV-6 reactivation. The presence of viral DNA in the follicle bulb confirmed the genomic integration and allowed the discontinuation of the antiviral treatment to the patient.  This case might be helpful for discriminate HHV-6 reactivation from viral integration, thus avoiding unnecessary and potentially toxic antiviral therapy once the genomic integration is confirmed.